Glass material, chemically strengthened glass, and method for producing same

By designing glass materials with specific components and performing chemical strengthening treatment, the challenges of chemical strengthening of high refractive index and high dispersion glass materials have been solved, resulting in high-quality and high-strength chemically strengthened glass suitable for high-performance optical equipment.

CN120965095APending Publication Date: 2025-11-18CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511289352.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In existing technologies, glass materials with high refractive index and high dispersion are difficult to chemically strengthen, or the surface quality after chemical strengthening is poor, which cannot meet the requirements for impact resistance and drop resistance in fields such as vehicle imaging and security monitoring.

Method used

Glass materials with specific component ratios, including SiO2, B2O3, ZrO2, La2O3, Nb2O5, ZnO, TiO2, RO, Rn2O, etc., are chemically strengthened to produce chemically strengthened glass, which meets the requirements of high refractive index and high dispersion, and generates a compressive stress layer on the glass surface through a specific ion exchange process.

Benefits of technology

The resulting chemically strengthened glass has good surface quality and high bending strength, making it suitable for high-performance optical equipment and meeting the impact resistance requirements of fields such as automotive imaging and security monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005589778360000181
    Figure BDA0005589778360000181
  • Figure BDA0005589778360000182
    Figure BDA0005589778360000182
  • Figure BDA0005589778360000191
    Figure BDA0005589778360000191
Patent Text Reader

Abstract

The invention provides a glass material with high refractive index and high dispersion, which comprises the following components in percentage by weight: 28.0-42.0% of SiO2; 1.0 to 9.5 percent of B2O3; zrO2: 1.0 to 10.0 percent; la2O3: greater than or equal to 1.0% but less than 10.0%; 2.0% to 14.5% of Nb2O5 (niobium oxide); 2.0 to 14.5 percent of ZnO (zinc oxide); 3.0 to 16.0% of TiO2 (titanium dioxide); 2.0 to 22.0% of RO (Reactive Oxygen); the content of ZnO / La2O3 is 0.30 to 8.00 percent, and the content of Rn2O is 2.0 to 24.0 percent. Through reasonable component design, the glass material disclosed by the invention has expected refractive index and Abbe number, is also suitable for being prepared into chemically strengthened glass with excellent performances such as better surface quality and higher bending strength through chemical strengthening treatment, and can be widely applied to various high-performance optical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a glass material, in particular to a glass material suitable for chemical strengthening, and a chemically strengthened glass and a glass element made therefrom. BACKGROUND

[0002] In recent years, glass materials with high refractive index and high dispersion (low Abbe number) are widely used in vehicle-mounted imaging, security monitoring and other fields. In the production of glass materials for glass elements, there is a high demand for glasses with high refractive index and high dispersion, which can achieve the lightweight and miniaturization of the overall optical system. At the same time, such glass materials have a very important significance in simplifying the optical system and improving the imaging quality in the field of optical design and optical communication.

[0003] The glass used in vehicle-mounted imaging, security monitoring and other fields has high requirements for impact resistance and drop resistance. Generally speaking, the main reason for low glass strength and poor impact resistance is that the glass fails due to crack propagation, and the stress required for the propagation of microcracks on the surface and subsurface of the glass is low. Regardless of the method used, it is difficult to completely eliminate the microcracks on the surface and subsurface of the glass, so the main way to improve the drop resistance and impact resistance of the glass is post-treatment strengthening. Post-treatment strengthening includes physical strengthening and chemical strengthening, and the effective mechanism is to generate a compressive stress layer on the surface of the glass to inhibit crack propagation. Physical strengthening is to heat the glass and rapidly cool it, so that the internal relaxation thermal stress is significantly slower than the surface, the internal relaxation thermal stress is greater than the surface, and a compressive stress is left on the surface of the glass to prevent the unstable propagation of surface microcracks, thereby improving the impact resistance of the glass. However, this method has high requirements for glass materials, especially for the strengthening of ultra-thin glass and glass with a large thermal expansion coefficient, so the application of physical strengthening is limited. Chemical strengthening is to use a molten salt containing monovalent or divalent metal ions with a large ionic radius to treat the surface of the glass, and the smaller radius ions in the glass undergo an ion exchange process with the molten salt, thereby generating a permanent compressive stress on the surface of the glass. Chemical strengthening is generally carried out below the glass transition temperature, which is not easy to cause deformation of the glass, and is widely used in glass thin applications such as mobile phone screens and smart wearable device screens. In the prior art, glass materials with high refractive index and high dispersion have the problems of being difficult to chemically strengthen or having poor surface quality after chemical strengthening. SUMMARY

[0004] Based on the above reasons, the technical problem to be solved by the present application is to provide a glass material with high refractive index and high dispersion, which is suitable for being made into a chemically strengthened glass by chemical strengthening treatment.

[0005] The technical solution adopted by the present application to solve the technical problem is:

[0006] (1) a glass material, the components of which, expressed in percentage by weight, comprise: SiO2: 28.0 to 42.0%; B2O3: 1.0 to 9.5%; ZrO2: 1.0 to 10.0%; La2O3: greater than or equal to 1.0% but less than 10.0%; Nb2O5: 2.0 to 14.5%; ZnO: 2.0 to 14.5%; TiO2: 3.0 to 16.0%; RO: 2.0 to 22.0%; Rn2O: 2.0 to 24.0%, with ZnO / La2O3 being between 0.30 and 8.00, said RO being the total content of MgO, CaO, SrO, BaO, and Rn2O being the total content of Li2O, Na2O, K2O.

[0007] (2) the glass material according to (1), the components of which, expressed in percentage by weight, further comprise: Al2O3: 0 to 8.0%; and / or Y2O3: 0 to 8.0%; and / or Gd2O3: 0 to 5.0%; and / or P2O5: 0 to 5.0%; and / or WO3: 0 to 3.0%; and / or a fining agent: 0 to 1.0%, said fining agent being one or more of Sb2O3, SnO, SnO2, CeO2.

[0008] (3) the glass material according to (1) or (2), the components of which, expressed in percentage by weight, satisfy one or more of the following 13 cases:

[0009] 1) ZnO / La2O3 is between 0.50 and 5.00, preferably ZnO / La2O3 is between 0.80 and 3.50, more preferably ZnO / La2O3 is between 1.00 and 2.50;

[0010] 2) SiO2 / (B2O3+BaO) is between 1.50 and 8.00, preferably SiO2 / (B2O3+BaO) is between 1.80 and 6.00, more preferably SiO2 / (B2O3+BaO) is between 2.00 and 5.50, further preferably SiO2 / (B2O3+BaO) is between 2.80 and 3.80;

[0011] 3) (ZnO+BaO) / SiO2 is between 0.10 and 0.80, preferably (ZnO+BaO) / SiO2 is between 0.20 and 0.70, more preferably (ZnO+BaO) / SiO2 is between 0.30 and 0.60;

[0012] 4) (Nb2O5+ ZrO2) / (ZnO + TiO2) is 0.30 to 3.00, preferably (Nb2O5+ ZrO2) / (ZnO + TiO2) is 0.35 to 2.00, more preferably (Nb2O5+ ZrO2) / (ZnO + TiO2) is 0.40 to 1.40, further preferably (Nb2O5+ ZrO2) / (ZnO + TiO2) is 0.50 to 1.00;

[0013] 5) (La2O3+ Na2O) / Nb2O5is 0.50 to 7.00, preferably (La2O3+ Na2O) / Nb2O5is 0.80 to 5.00, more preferably (La2O3+ Na2O) / Nb2O5is 1.00 to 3.50, further preferably (La2O3+ Na2O) / Nb2O5is 1.10 to 2.00;

[0014] 6) (La2O3+ BaO) / Na2O is 0.30 to 7.00, preferably (La2O3+ BaO) / Na2O is 0.50 to 5.00, more preferably (La2O3+ BaO) / Na2O is 0.80 to 3.00, further preferably (La2O3+ BaO) / Na2O is 1.00 to 2.50;

[0015] 7) (Nb2O5+ TiO2+ CaO) / SiO2is 0.15 to 1.00, preferably (Nb2O5+ TiO2+ CaO) / SiO2is 0.20 to 0.80, more preferably (Nb2O5+ TiO2+ CaO) / SiO2is 0.30 to 0.70;

[0016] 8) La2O3 / TiO2is 0.20 to 2.50, preferably La2O3 / TiO2is 0.20 to 2.00, more preferably La2O3 / TiO2is 0.30 to 1.50, further preferably La2O3 / TiO2is 0.30 to 1.00;

[0017] 9) Y2O3 / Na2O is 0.05 to 2.00, preferably Y2O3 / Na2O is 0.08 to 1.50, more preferably Y2O3 / Na2O is 0.10 to 1.00, further preferably Y2O3 / Na2O is 0.10 to 0.70;

[0018] 10) Y2O3 / SrO is 0.10 to 5.00, preferably Y2O3 / SrO is 0.20 to 4.00, more preferably Y2O3 / SrO is 0.30 to 2.00, further preferably Y2O3 / SrO is 0.40 to 1.00;

[0019] 11)(Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 1.00~9.00, preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.00~7.50, more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.50~6.00, and even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 3.20~4.80;

[0020] 12) The ratio of 5×P2O5 / Al2O3 is 0.10 to 6.00, preferably 0.20 to 3.50, more preferably 0.30 to 2.50, and even more preferably 0.50 to 1.50;

[0021] 13) The ratio of (Li2O+K2O) / Al2O3 is 0.20 to 5.00, preferably 0.50 to 3.50, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50.

[0022] (4) The glass material according to (1) or (2) comprises, in weight percentage: SiO2: 30.5-39.5%, preferably SiO2: 32.0-37.0%; and / or B2O3: 2.0-8.0%, preferably B2O3: 2.5-7.0%; and / or ZrO2: 2.0-8.5%, preferably ZrO2: 3.0-7.0%; and / or La2O3: 2.0-9.0%, preferably La2O3 3.0–8.0%; and / or Nb2O5: 4.0–12.0%, preferably Nb2O5: 5.0–10.0%; and / or ZnO: 4.0–12.0%, preferably ZnO: 5.0–10.0%; and / or TiO2: 5.0–15.0%, preferably TiO2: 7.0–13.0%; and / or RO: 3.0–18.0%, preferably RO: 5.0–15.0%; and / or Rn2O: 5.0–20% 0.0%, preferably Rn2O: 7.0-15.0%; and / or Al2O3: 0.1-6.0%, preferably Al2O3: 0.5-4.0%; and / or Y2O3: greater than 0% but less than or equal to 6.0%, preferably Y2O3: 0.1-4.0%; and / or Gd2O3: 0-3.0%, preferably Gd2O3: 0-1.0%, more preferably Gd2O3-free; and / or P2O5: 0-3.0%, preferably P2O5: Greater than 0% but less than or equal to 2.0%; and / or WO3: 0 to 2.0%, preferably WO3: 0 to 1.0%, more preferably WO3-free; and / or clarifying agent: 0 to 0.5%, preferably 0 to 0.2%, wherein RO is the total content of MgO, CaO, SrO, and BaO, Rn2O is the total content of Li2O, Na2O, and K2O, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

[0023] (5) The glass material according to (1) or (2), wherein the components are expressed in weight percentages, wherein: BaO: 1.0–12.0%, preferably BaO: 2.0–10.0%, more preferably BaO: 3.0–8.0%; and / or SrO: 0–10.0%, preferably SrO: 0.5–8.0%, more preferably SrO: 1.0–6.0%; and / or CaO: 0–5.0%, preferably CaO: 0–3.0%, more preferably CaO: 0–2.0%, further preferably free of CaO; and / or MgO: 0–5.0%, preferably MgO: 0–4.0%, more preferably MgO: 0–2.0%, even more preferably MgO-free; and / or Li2O: greater than 0% but less than or equal to 8.0%, preferably Li2O: greater than 0% but less than or equal to 6.0%, more preferably Li2O: 0.1–4.0%; and / or Na2O: 2.0–15.0%, preferably Na2O: 4.0–12.0%, more preferably Na2O: 5.0–10.0%; and / or K2O: greater than 0% but less than or equal to 8.0%, preferably K2O: 0.1–6.0%, more preferably K2O: 0.5–4.5%.

[0024] (6) The glass material according to (1) or (2), wherein the refractive index n of the glass material is... d The value is 1.660–1.740, preferably 1.670–1.730, more preferably 1.680–1.710; and / or the Abbe number v d The content is 31.00–38.00, preferably 32.00–37.00, more preferably 34.00–36.50; and / or the density ρ is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 The following are required: and / or weather resistance (CR) is Class 2 or above, preferably Class 1; and / or water resistance stability (D). W It is classified as Class 2 or above, preferably Class 1; and / or acid resistance stability D A It is of two or more classes, preferably of one class; and / or the coefficient of thermal expansion α -30 / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K below; and / or transition temperature T g Temperature is below 590°C, preferably below 580°C, and more preferably below 570°C; and / or Knoop hardness H K 520×10 7 Pa or higher, preferably 540 × 10 Pa 7 Pa or higher, more preferably 550 × 10 Pa 7Pa or above; and / or Young's modulus E is 8500 × 10⁻⁶. 7 Pa or higher, preferably 9000×10 Pa 7 Pa or higher, more preferably 9200 × 10 Pa 7 Pa or above; and / or λ 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80 The wavelength is 410 nm or less; and / or λ5 is 375 nm or less, preferably 365 nm or less, more preferably 360 nm or less; and / or the bubble density is A grade or higher, preferably A0 grade or higher, more preferably A. 00 class.

[0025] (7) Glass preforms, made of any of the glass materials described in (1) to (6).

[0026] (8) Chemically strengthened glass, made of any of the glass materials described in (1) to (6), or made of the glass preform described in (7).

[0027] (9) The chemically strengthened glass according to (8), wherein the strengthening layer depth of the chemically strengthened glass is 15 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 to 50 μm; and / or the bending strength is 250 MPa or more, preferably 300 MPa or more, more preferably 350 MPa or more, and even more preferably 450 to 500 MPa; and / or the drop ball test height is 1.0 m or more, preferably 1.3 m or more, more preferably 1.5 m or more, and even more preferably 1.8 m or more; and / or the surface quality is Class 2 or more, preferably Class 1 or more.

[0028] (10) Chemically strengthened glass, the composition of which is expressed as a weight percentage, contains: SiO2: 28.0-42.0%; B2O3: 1.0-9.5%; ZrO2: 1.0-10.0%; La2O3: greater than or equal to 1.0% but less than 10.0%; Nb2O5: 2.0-14.5%; ZnO: 2.0-14.5%; TiO2: 3.0-16.0%; RO: 2.0-22.0%; Rn2O: 2.0-24.0%, wherein ZnO / La2O3 is 0.30-8.00, wherein RO is the total content of MgO, CaO, SrO and BaO, and Rn2O is the total content of Li2O, Na2O and K2O.

[0029] (11) The chemically strengthened glass according to (10), wherein the components, expressed as weight percentages, further contain: Al2O3: 0-8.0%; and / or Y2O3: 0-8.0%; and / or Gd2O3: 0-5.0%; and / or P2O5: 0-5.0%; and / or WO3: 0-3.0%; and / or clarifier: 0-1.0%, wherein the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.

[0030] (12) The chemically strengthened glass according to (10) or (11) has a composition expressed as a weight percentage that satisfies one or more of the following 13 conditions:

[0031] 1) The ZnO / La2O3 ratio is 0.50 to 5.00, preferably 0.80 to 3.50, and more preferably 1.00 to 2.50;

[0032] 2) The SiO2 / (B2O3+BaO) ratio is 1.50 to 8.00, preferably 1.80 to 6.00, more preferably 2.00 to 5.50, and even more preferably 2.80 to 3.80;

[0033] 3) The ratio of (ZnO+BaO) / SiO2 is 0.10 to 0.80, preferably 0.20 to 0.70, and more preferably 0.30 to 0.60;

[0034] 4) The ratio of (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.30~3.00, preferably 0.35~2.00, more preferably 0.40~1.40, and even more preferably 0.50~1.00;

[0035] 5) The ratio of (La2O3+Na2O) / Nb2O5 is 0.50 to 7.00, preferably 0.80 to 5.00, more preferably 1.00 to 3.50, and even more preferably 1.10 to 2.00;

[0036] 6) The ratio of (La2O3+BaO) / Na2O is 0.30 to 7.00, preferably 0.50 to 5.00, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50;

[0037] 7) The ratio of (Nb2O5+TiO2+CaO) / SiO2 is 0.15 to 1.00, preferably 0.20 to 0.80, and more preferably 0.30 to 0.70.

[0038] 8) The La2O3 / TiO2 ratio is 0.20 to 2.50, preferably 0.20 to 2.00, more preferably 0.30 to 1.50, and even more preferably 0.30 to 1.00;

[0039] 9) The Y2O3 / Na2O ratio is 0.05 to 2.00, preferably 0.08 to 1.50, more preferably 0.10 to 1.00, and even more preferably 0.10 to 0.70;

[0040] 10) The Y2O3 / SrO ratio is 0.10 to 5.00, preferably 0.20 to 4.00, more preferably 0.30 to 2.00, and even more preferably 0.40 to 1.00;

[0041] 11)(Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 1.00~9.00, preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.00~7.50, more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.50~6.00, and even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 3.20~4.80;

[0042] 12) The ratio of 5×P2O5 / Al2O3 is 0.10 to 6.00, preferably 0.20 to 3.50, more preferably 0.30 to 2.50, and even more preferably 0.50 to 1.50;

[0043] 13) The ratio of (Li2O+K2O) / Al2O3 is 0.20 to 5.00, preferably 0.50 to 3.50, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50.

[0044] (13) The chemically strengthened glass according to (10) or (11), wherein the composition is expressed as a weight percentage, wherein: SiO2: 30.5-39.5%, preferably SiO2: 32.0-37.0%; and / or B2O3: 2.0-8.0%, preferably B2O3: 2.5-7.0%; and / or ZrO2: 2.0-8.5%, preferably ZrO2: 3.0-7.0%; and / or La2O3: 2.0-9.0%, preferably La2O3: 2.0-9.0%. a₂O₃: 3.0–8.0%; and / or Nb₂O₅: 4.0–12.0%, preferably Nb₂O₅: 5.0–10.0%; and / or ZnO: 4.0–12.0%, preferably ZnO: 5.0–10.0%; and / or TiO₂: 5.0–15.0%, preferably TiO₂: 7.0–13.0%; and / or RO: 3.0–18.0%, preferably RO: 5.0–15.0%; and / or Rn₂O: 5.0% ~20.0%, preferably Rn2O: 7.0~15.0%; and / or Al2O3: 0.1~6.0%, preferably Al2O3: 0.5~4.0%; and / or Y2O3: greater than 0% but less than or equal to 6.0%, preferably Y2O3: 0.1~4.0%; and / or Gd2O3: 0~3.0%, preferably Gd2O3: 0~1.0%, more preferably Gd2O3-free; and / or P2O5: 0~3.0%, preferably P2O 5: greater than 0% but less than or equal to 2.0%; and / or WO3: 0 to 2.0%, preferably WO3: 0 to 1.0%, more preferably WO3-free; and / or clarifying agent: 0 to 0.5%, preferably 0 to 0.2%, wherein RO is the total content of MgO, CaO, SrO, and BaO, Rn2O is the total content of Li2O, Na2O, and K2O, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

[0045] (14) The chemically strengthened glass according to (10) or (11), wherein the components are expressed in weight percentages, wherein: BaO: 1.0–12.0%, preferably BaO: 2.0–10.0%, more preferably BaO: 3.0–8.0%; and / or SrO: 0–10.0%, preferably SrO: 0.5–8.0%, more preferably SrO: 1.0–6.0%; and / or CaO: 0–5.0%, preferably CaO: 0–3.0%, more preferably CaO: 0–2.0%, further preferably free of CaO; and / or MgO: 0–5.0%, preferably MgO. O: 0-4.0%, more preferably MgO: 0-2.0%, even more preferably MgO-free; and / or Li2O: greater than 0% but less than or equal to 8.0%, preferably Li2O: greater than 0% but less than or equal to 6.0%, more preferably Li2O: 0.1-4.0%; and / or Na2O: 2.0-15.0%, preferably Na2O: 4.0-12.0%, more preferably Na2O: 5.0-10.0%; and / or K2O: greater than 0% but less than or equal to 8.0%, preferably K2O: 0.1-6.0%, more preferably K2O: 0.5-4.5%.

[0046] (15) The chemically strengthened glass according to (10) or (11), wherein the refractive index n of the chemically strengthened glass is... d The value is 1.660–1.740, preferably 1.670–1.730, more preferably 1.680–1.710; and / or the Abbe number v d The content is 31.00–38.00, preferably 32.00–37.00, more preferably 34.00–36.50; and / or the density ρ is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 The following are required: and / or weather resistance (CR) is Class 2 or above, preferably Class 1; and / or water resistance stability (D). W It is classified as Class 2 or above, preferably Class 1; and / or acid resistance stability D A It is of two or more classes, preferably of one class; and / or the coefficient of thermal expansion α -30 / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K below; and / or transition temperature T g The temperature is below 590°C, preferably below 580°C, and more preferably below 570°C; and / or λ 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80The wavelength is 410 nm or less; and / or λ5 is 375 nm or less, preferably 365 nm or less, more preferably 360 nm or less; and / or the bubble density is A grade or higher, preferably A0 grade or higher, more preferably A. 00 Grade; and / or the depth of the reinforcing layer is 15 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 to 50 μm; and / or the flexural strength is 250 MPa or more, preferably 300 MPa or more, more preferably 350 MPa or more, and even more preferably 450 to 500 MPa; and / or the drop ball test height is 1.0 m or more, preferably 1.3 m or more, more preferably 1.5 m or more, and even more preferably 1.8 m or more; and / or the surface quality is Class 2 or more, preferably Class 1 or more.

[0047] (16) A glass element made of any of the glass materials described in (1) to (6), or a glass preform described in (7), or a chemically strengthened glass described in (8) to (15).

[0048] (17) An optical device comprising any of the glass materials described in (1) to (6), or any of the chemically strengthened glass described in (8) to (15), or a glass element described in (16).

[0049] The method for manufacturing chemically strengthened glass according to any one of (18)(8) to (15) includes the following steps: forming a glass material, chemically strengthening the glass material, or chemically strengthening the glass material after processing it into a glass preform.

[0050] (19) According to the method for manufacturing chemically strengthened glass as described in (18), the chemical strengthening treatment includes immersing the glass material or glass preform in a molten salt containing KNO3 and / or NaNO3 for two-step chemical strengthening. The first step of chemical strengthening includes immersing the glass material or glass preform in a molten salt containing NaNO3. The temperature of the first step of chemical strengthening is 400-500°C, preferably 420-480°C, more preferably 430-470°C. The time of the first step of chemical strengthening is 1-11 hours, preferably 1-9 hours, more preferably 1-7 hours. The second step of chemical strengthening includes immersing the glass material or glass preform after the first step of chemical strengthening in a molten salt containing KNO3. The temperature of the second step of chemical strengthening is 420-520°C, preferably 440-500°C, more preferably 450-490°C. The time of the second step of chemical strengthening is 10 minutes to 2.5 hours, preferably 20 minutes to 2 hours.

[0051] The beneficial effects of this invention are: through reasonable component design, the glass material obtained by this invention, while possessing the desired refractive index and Abbe number, is also suitable for chemical strengthening treatment to produce chemically strengthened glass. The chemically strengthened glass obtained by this invention has excellent properties such as good surface quality and high bending strength, and can be widely used in various high-performance optical devices. Detailed Implementation

[0052] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of the present invention. Furthermore, while there are appropriate omissions in the repeated descriptions, this does not limit the spirit of the invention. In this specification, glass before chemical strengthening is referred to as glass material or glass or pre-strengthened glass, and glass or glass preforms after chemical strengthening are referred to as chemically strengthened glass or post-strengthened glass.

[0053] [Glass Materials and Chemically Strengthened Glass]

[0054] The component ranges of the glass material and chemically strengthened glass of the present invention are described below. In the present invention, unless otherwise specified, the content, total content, and total amount of each component are expressed as weight percentages (wt%), that is, the weight percentage of the content, total content, and total amount of each component relative to the total amount of the glass or chemically strengthened glass material converted into oxide composition. Here, "converted into oxide composition" means that when the oxides, complex salts, and hydroxides used as raw materials for the glass material or chemically strengthened glass of the present invention decompose and transform into oxides upon melting, the total amount of such oxides is taken as 100%.

[0055] Unless otherwise specified in the specific context, the numerical ranges listed in this invention include upper and lower limits, and "above" and "below" include endpoint values ​​and all integers and fractions included in the range, but are not limited to the specific values ​​listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.

[0056] <Essential and Optional Components>

[0057] SiO2 is the framework of glass materials and chemically strengthened glass. As a glass network generator, it plays a role in maintaining the chemical stability of glass, improving its resistance to devitrification, and reducing its high-temperature viscosity. In this invention, the above effects are achieved by containing 28.0% or more SiO2, preferably 30.5% or more, and more preferably 32.0% or more. If the SiO2 content exceeds 42.0%, the glass meltability decreases, making it difficult to process the glass raw materials and easily leading to internal quality problems such as stone formation. Simultaneously, the glass transition temperature increases, and excessively high melting temperatures also result in poor light transmittance. Therefore, the SiO2 content is 42.0% or less, preferably 39.5% or less, and more preferably 37.0% or less. In some embodiments, the SiO2 content can be 28.0%, 28.5%, 29.0%, 29.5%, 30.0%, 30.5%, 31.0%, 31.5%, 32.0%, 32.5%, 33.0%, 33.5%, 34.0%, 34.5%, 35.0%, 35.5%, 36.0%, 36.5%, 37.0%, 37.5%, 38.0%, 38.5%, 39.0%, 39.5%, 40.0%, 40.5%, 41.0%, 41.5%, 42.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0058] B2O3 can improve the melt flow properties and devitrification resistance of glass, which is beneficial for lowering the glass transition temperature. When present in appropriate amounts, it can improve the glass network strength. However, if its content is too high, it will damage the network structure, reduce the chemical stability of the glass, hinder the adjustment of optical constants, increase the abrasion resistance, reduce the hardness, and negatively impact the chemical strengthening properties of the glass. Therefore, the B2O3 content in this invention is 1.0–9.5%, preferably 2.0–8.0%, and more preferably 2.5–7.0%. In some embodiments, the B2O3 content can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, etc., as well as all ranges and subranges between these values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0059] Al2O3 can improve the chemical stability, mechanical strength, and weather resistance of glass, and can expand ion exchange channels to enhance chemical strengthening. However, if its content is too high, the meltability of the glass decreases and its resistance to crystallization deteriorates. Therefore, the content of Al2O3 is 0–8.0%, preferably 0.1–6.0%, and more preferably 0.5–4.0%. In some embodiments, the Al2O3 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0060] ZrO2 is a network intermediate component that can increase the refractive index of glass. When there is sufficient free oxygen in the glass, it can enter the glass network structure, thereby improving the glass's resistance to crystallization, chemical stability, and mechanical properties. It can also increase the glass's viscosity and visible light transmittance. However, due to the high melting point of ZrO2, if its content is too high, it will lead to an increase in the glass's melting temperature and liquidus temperature, a decrease in the glass's resistance to devitrification, and the formation of inclusions within the glass, affecting its internal quality. Therefore, in this invention, the ZrO2 content is 1.0–10.0%, preferably 2.0–8.5%, and more preferably 3.0–7.0%. In some embodiments, the ZrO2 content can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0061] La2O3 can increase the refractive index of glass, improving its resistance to devitrification and chemical stability. In this invention, the above effects are achieved by containing 1.0% or more La2O3, preferably 2.0% or more, and more preferably 3.0% or more. If the La2O3 content is too high, the hardness of the glass decreases, its resistance to crystallization deteriorates, and its density increases. Therefore, the La2O3 content is less than 10.0%, preferably 9.0% or less, and more preferably 8.0% or less. In some embodiments, the La2O3 content can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 9.6%, 9.8%, less than 10.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0062] Gd₂O₃ can improve the refractive index and chemical stability of glass, but if its content exceeds 5.0%, the glass's resistance to devitrification and abrasion deteriorates, and the raw material cost of the glass increases. Therefore, the content of Gd₂O₃ is 0–5.0%, preferably 0–3.0%, and more preferably 0–1.0%. In some embodiments, it is further preferred that the glass does not contain Gd₂O₃. In some embodiments, the content of Gd₂O₃ can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0063] Y₂O₃ can improve the refractive index and devitrification resistance of glass, and adjust the Young's modulus of glass. However, if its content is too high, the chemical stability and weather resistance of the glass will deteriorate. Therefore, the Y₂O₃ content in this invention is 0-8.0%, preferably greater than 0% but less than or equal to 6.0%, and more preferably 0.1-4.0%. In some embodiments, the content of Y₂O₃ can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0064] Nb₂O₅ can improve the refractive index and dispersion of glass, and enhance its chemical stability and devitrification resistance. In this invention, the above effects are achieved by containing 2.0% or more Nb₂O₅, preferably 4.0% or more, and more preferably 5.0% or more. If the Nb₂O₅ content is too high, the short-wave transmittance in the visible light region of the glass decreases, the glass density increases, and the raw material cost of the glass rises. Therefore, in this invention, the Nb₂O₅ content is 14.5% or less, preferably 12.0% or less, and more preferably 10.0% or less. In some embodiments, the Nb₂O₅ content can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0065] Alkaline earth metal oxides (RO, representing the total content of MgO, CaO, SrO, and BaO) can adjust the optical constants of glass and optimize its devitrification resistance. However, when their content is too high, the chemical stability of the glass decreases, and its chemical strengthening properties deteriorate. Therefore, the RO content is 2.0%–22.0%, preferably 3.0%–18.0%, and more preferably 5.0%–15.0%. In some embodiments, the RO content can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%. 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0066] Since the alkaline earth metal oxides MgO, CaO, SrO, and BaO play significantly different roles in glass, their contents in the glass of this invention also vary.

[0067] BaO can improve the devitrification resistance and hardness of glass, and reduce the temperature coefficient of refractive index and the coefficient of thermal expansion of glass. In this invention, the above effects are achieved by containing more than 1.0% BaO, preferably more than 2.0%, and more preferably more than 3.0%. On the other hand, by keeping the BaO content below 12.0%, the decrease in chemical stability caused by excessive BaO content can be prevented. Preferably, the BaO content is below 10.0%, and more preferably below 8.0%. In some embodiments, the BaO content can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0068] In some embodiments, by controlling the ratio of SiO2 content to the total content of B2O3 and BaO (B2O3+BaO), SiO2 / (B2O3+BaO), within the range of 1.50 to 8.00, it is possible to improve the bubble count of the glass while preventing an increase in the coefficient of thermal expansion, and it is also beneficial to improve the flexural strength of chemically strengthened glass. Therefore, it is preferable that SiO2 / (B2O3+BaO) is 1.50 to 8.00, more preferably 1.80 to 6.00, further preferably 2.00 to 5.50, and even more preferably 2.80 to 3.80. In some embodiments, SiO2 / (B2O3+BaO) can be 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4... 70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, 6.60, 6.70, 6.80, 6.90, 7.00, 7.10, 7.20, 7.30, 7.40, 7.50, 7.60, 7.70, 7.80, 7.90, 8.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0069] CaO is a component that improves the devitrification resistance and reduces the abrasion resistance of glass, and is an optional component in the glass of this invention. In this invention, by keeping the CaO content below 5.0%, the devitrification resistance of the glass can be improved while suppressing the decrease in the glass's refractive index. Therefore, the CaO content is 0–5.0%, preferably 0–3.0%, and more preferably 0–2.0%. In some embodiments, it is further preferred that the glass does not contain CaO. In some embodiments, the CaO content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0070] SrO can adjust the refractive index and Abbe number of glass, and can also improve the glass's resistance to devitrification, light transmittance, chemical stability, and mechanical properties. However, if its content is too high, the glass's resistance to crystallization deteriorates. Therefore, the SrO content is 0–10.0%, preferably 0.5–8.0%, and more preferably 1.0–6.0%. In some embodiments, the SrO content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0071] In some embodiments, controlling the ratio of Y₂O₃ content to SrO content, Y₂O₃ / SrO, within the range of 0.10 to 5.00 can improve the hardness of the glass while preventing a deterioration in its water resistance. Therefore, a Y₂O₃ / SrO ratio of 0.10 to 5.00 is preferred, more preferably 0.20 to 4.00, even more preferably 0.30 to 2.00, and still more preferably 0.40 to 1.00. In some implementations, the Y₂O₃ / SrO ratio can be 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, or 1. 80, 1.85, 1.90, 1.95, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0072] MgO can reduce the relative partial dispersion of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-crystallization performance and stability of the glass decrease. Therefore, the MgO content is 0-5.0%, preferably 0-4.0%, and more preferably 0-2.0%. In some embodiments, it is further preferred that the glass does not contain MgO. In some embodiments, the MgO content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0073] ZnO can increase the refractive index of glass, lower its transition temperature and coefficient of thermal expansion, improve its thermal stability, and enhance its chemical stability. However, if the ZnO content is too high, the glass's abrasion resistance increases, its hardness decreases, which is detrimental to maintaining its anti-crystallization stability and high transmittance, and also negatively impacts its chemical strengthening properties. Therefore, the ZnO content is 2.0–14.5%, preferably 4.0–12.0%, and more preferably 5.0–10.0%. In some embodiments, the ZnO content can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0074] In some embodiments, controlling the ratio of ZnO content to La2O3 content (ZnO / La2O3) within the range of 0.30 to 8.00 is beneficial for improving the light transmittance and devitrification resistance of the glass, as well as enhancing its chemical strengthening properties. Therefore, a ZnO / La2O3 ratio of 0.30 to 8.00 is preferred, more preferably 0.50 to 5.00, even more preferably 0.80 to 3.50, and still more preferably 1.00 to 2.50. In some implementations, the ZnO / La2O3 content can be 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, or 3.60. The values ​​are 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.30, 6.50, 6.70, 7.00, 7.10, 7.30, 7.50, 7.70, 8.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0075] In some embodiments, the ratio of the total ZnO and BaO content (ZnO+BaO) to the SiO2 content (ZnO+BaO) / SiO2 is controlled within the range of 0.10 to 0.80. This can reduce the coefficient of thermal expansion of the glass while preventing a deterioration in the Young's modulus and improving the flexural strength of the chemically strengthened glass. Therefore, it is preferable that (ZnO+BaO) / SiO2 is 0.10 to 0.80, more preferably 0.20 to 0.70, and even more preferably 0.30 to 0.60. In some implementations, (ZnO+BaO) / SiO2 can be 0.10, 0.11, 0.13, 0.15, 0.17, 0.20, 0.21, 0.23, 0.25, 0.27, 0.30, 0.31, 0.33, 0.35, 0.37, 0.40, 0.41, 0.43, 0.45, 0.47, 0.50, 0.51, 0.53, 0.55, 0.57, 0.60, 0.61, 0.63, 0.65, 0.67, 0.70, 0.71, 0.73, 0.75, 0.77, 0.80, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0076] Alkali metal oxides Rn₂O (Rn₂O being the total content of Li₂O, Na₂O, and K₂O) can lower the glass transition temperature, adjust the optical constants and high-temperature viscosity of the glass, and improve the glass's meltability. However, high Rn₂O content reduces the glass's resistance to devitrification and chemical stability. Therefore, the Rn₂O content in this invention is 2.0%–24.0%, preferably 5.0%–20.0%, and more preferably 7.0%–15.0%. In some embodiments, the Rn₂O content can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, and 13.5%. 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0077] Since alkali metal oxides Li2O, Na2O, and K2O play significantly different roles in glass, their contents in the glass of this invention also vary.

[0078] Li₂O can lower the glass transition temperature, adjust the high-temperature viscosity of glass, and improve the melting properties of glass. It is the main component used for ion exchange in the chemical strengthening process of the glass material of this invention. However, a high content of Li₂O is detrimental to the chemical stability of the glass and the economic efficiency of raw material costs. Therefore, the content of Li₂O in this invention is greater than 0% but less than or equal to 8.0%, preferably greater than 0% but less than or equal to 6.0%, and more preferably 0.1% to 4.0%. In some embodiments, the Li₂O content can be greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0079] Na₂O can improve the melt flow properties and light transmittance of glass, and is the main component used for ion exchange in the chemical strengthening process of the glass material of this invention. In this invention, the above-mentioned effects are achieved by containing 2.0% or more Na₂O, preferably 4.0% or more, and more preferably 5.0% or more. However, if the Na₂O content is too high, the coefficient of thermal expansion of the glass increases, and its chemical stability decreases. Therefore, the Na₂O content is 15.0% or less, preferably 12.0% or less, and more preferably 10.0% or less. In some embodiments, the Na₂O content can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0080] In some embodiments, controlling the ratio of Y₂O₃ content to Na₂O content, Y₂O₃ / Na₂O, within the range of 0.05 to 2.00 is beneficial for improving the acid resistance and weather resistance of the glass, and also for improving the surface quality of chemically strengthened glass. Therefore, a Y₂O₃ / Na₂O ratio of 0.05 to 2.00 is preferred, more preferably 0.08 to 1.50, further preferably 0.10 to 1.00, and even more preferably 0.10 to 0.70. In some implementations, Y₂O₃ / Na₂O can be 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0081] In some embodiments, the content of La2O3 and Na2O, specifically the ratio of La2O3+Na2O to Nb2O5 (La2O3+Na2O) / Nb2O5, is controlled within the range of 0.50 to 7.00. This can improve the hardness of the glass while preventing a deterioration in its water resistance. Therefore, it is preferable that (La2O3+Na2O) / Nb2O5 is 0.50 to 7.00, more preferably 0.80 to 5.00, even more preferably 1.00 to 3.50, and still more preferably 1.10 to 2.00. In some implementations, (La₂O₃+Na₂O) / Nb₂O₅ can be 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, or 3. 40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.30, 6.50, 6.70, 7.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0082] In some embodiments, by controlling the ratio of the total content of La2O3 and BaO (La2O3+BaO) to the content of Na2O (La2O3+BaO) / Na2O within the range of 0.30 to 7.00, the glass transition temperature can be reduced and the bubble count of the glass can be improved. Therefore, it is preferable that (La2O3+BaO) / Na2O is 0.30 to 7.00, more preferably (La2O3+BaO) / Na2O is 0.50 to 5.00, further preferably (La2O3+BaO) / Na2O is 0.80 to 3.00, and even more preferably (La2O3+BaO) / Na2O is 1.00 to 2.50. In some implementations, the ratio of (La₂O₃+BaO) / Na₂O can be 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, or 3.3. 0, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.30, 6.50, 6.70, 7.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0083] In some embodiments, the ratio of the total content of Nb2O5, Na2O, La2O3, and Y2O3 (Nb2O5+Na2O+La2O3+Y2O3) to the total content of BaO and CaO (BaO+CaO) (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is controlled within the range of 1.00 to 9.00, which can increase the hardness of the glass while reducing its density. Therefore, the preferred ratio of (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 1.00 to 9.00, more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.00 to 7.50, even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.50 to 6.00, and even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 3.20 to 4.80. In some implementations, (Nb₂O₅+Na₂O+La₂O₃+Y₂O₃) / (BaO+CaO) can be 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, or 4. The values ​​are 00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.30, 6.50, 6.70, 7.00, 7.10, 7.30, 7.50, 7.70, 8.00, 8.10, 8.30, 8.50, 8.70, 9.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0084] K₂O improves the thermal stability and melting properties of glass. When present in appropriate amounts, it enhances the surface quality of chemically strengthened glass. However, excessive K₂O content deteriorates the chemical strengthening properties, devitrification resistance, and chemical stability of the glass. Therefore, in this invention, the K₂O content is greater than 0% but less than or equal to 8.0%, preferably 0.1–6.0%, and more preferably 0.5–4.5%. In some embodiments, the K2O content can be greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0085] In some embodiments, controlling the ratio of the total content of Li2O and K2O (Li2O+K2O) to the content of Al2O3 (Li2O+K2O) / Al2O3 within the range of 0.20 to 5.00 is beneficial for reducing the density of the glass and improving its weather resistance. Therefore, it is preferable that (Li2O+K2O) / Al2O3 is 0.20 to 5.00, more preferably 0.50 to 3.50, further preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50. In some implementations, the ratio of (Li₂O+K₂O) / Al₂O₃ can be 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, or 2.5. 0, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0086] TiO2 improves the refractive index and dispersion of glass, and its appropriate content can enhance the glass's resistance to crystallization and its chemical stability. In this invention, the above effects are achieved by containing 3.0% or more TiO2, preferably 5.0% or more, and more preferably 7.0% or more. If the TiO2 content is too high, the glass's devitrification resistance decreases, and the visible light transmittance of the glass also decreases. Therefore, in this invention, the TiO2 content is 16.0% or less, preferably 15.0% or less, and more preferably 13.0% or less. In some embodiments, the TiO2 content can be 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0087] In some embodiments, controlling the ratio of La2O3 content to TiO2 content (La2O3 / TiO2) within the range of 0.20 to 2.50 can increase the Young's modulus of the glass while lowering its transition temperature. Therefore, a La2O3 / TiO2 ratio of 0.20 to 2.50 is preferred, more preferably 0.20 to 2.00, even more preferably 0.30 to 1.50, and still more preferably 0.30 to 1.00. In some implementations, the La2O3 / TiO2 ratio can be 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1 0.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0088] In some embodiments, the ratio of the total content of Nb2O5 and ZrO2 (Nb2O5+ZrO2) to the total content of ZnO and TiO2 (ZnO+TiO2), (Nb2O5+ZrO2) / (ZnO+TiO2), is controlled within the range of 0.30 to 3.00. This can reduce the glass density while preventing the glass's weather resistance from deteriorating, and it is also beneficial for improving the drop ball test height of chemically strengthened glass. Therefore, the preferred ratio of (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.30 to 3.00, more preferably (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.35 to 2.00, even more preferably (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.40 to 1.40, and even more preferably (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.50 to 1.00. In some implementations, (Nb₂O₅+ZrO₂) / (ZnO+TiO₂) can be 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, or 1.55. The ranges are 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0089] In some embodiments, by controlling the ratio (Nb2O5+TiO2+CaO) / SiO2 between the total content of Nb2O5, TiO2, and CaO (Nb2O5+TiO2+CaO) and the content of SiO2 (Nb2O5+TiO2+CaO) / SiO2 within the range of 0.15 to 1.00, the weather resistance of the glass can be improved while preventing a deterioration in the Young's modulus. Therefore, it is preferable that (Nb2O5+TiO2+CaO) / SiO2 is 0.15 to 1.00, more preferably (Nb2O5+TiO2+CaO) / SiO2 is 0.20 to 0.80, and even more preferably (Nb2O5+TiO2+CaO) / SiO2 is 0.30 to 0.70. In some embodiments, the ratio of (Nb₂O₅+TiO₂+CaO) / SiO₂ can be 0.15, 0.17, 0.19, 0.20, 0.21, 0.23, 0.25, 0.27, 0.29, 0.30, 0.31, 0.33, 0.35, 0.37, 0.39, 0.40, 0.41, 0.43, 0.45, 0.47, 0.49, 0.50, 0.51, 0.53, or 0.5. 5, 0.57, 0.59, 0.60, 0.61, 0.63, 0.65, 0.67, 0.69, 0.70, 0.71, 0.73, 0.75, 0.77, 0.79, 0.80, 0.81, 0.83, 0.85, 0.87, 0.89, 0.90, 0.91, 0.93, 0.95, 0.97, 0.99, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0090] An appropriate amount of P2O5 can improve the thermal stability of glass and lower the melting temperature of glass raw materials, but if its content is too high, the glass's resistance to devitrification will deteriorate. Therefore, the P2O5 content is 0-5.0%, preferably 0-3.0%, and more preferably greater than 0% but less than or equal to 2.0%. In some embodiments, the P2O5 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0091] In some embodiments, controlling the 5×P2O5 / Al2O3 ratio within the range of 0.10 to 6.00 is beneficial for improving the bubble count of the glass and preventing a decrease in its acid resistance. Therefore, it is preferable that the 5×P2O5 / Al2O3 ratio is 0.10 to 6.00, more preferably 0.20 to 3.50, even more preferably 0.30 to 2.50, and still more preferably 0.50 to 1.50. In some implementations, 5×P2O5 / Al2O3 can be 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, or 3. 00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5.50, 5.60, 5.70, 5.80, 5.90, 6.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0092] WO3 can improve the refractive index and dispersion of glass. If the WO3 content exceeds 3.0%, the thermal stability and devitrification resistance of the glass decrease. Therefore, the WO3 content is 0-3.0%, preferably 0-2.0%, and more preferably 0-1.0%. In some embodiments, it is further preferred that the glass does not contain WO3. In some embodiments, the WO3 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0093] In this invention, one or more components selected from Sb₂O₃, SnO, SnO₂, and CeO₂, containing 0-1.0% as a clarifying agent, can improve the clarification effect of glass and increase its bubble level. Preferably, the content of the clarifying agent is 0-0.5%, more preferably 0-0.2%. When the Sb₂O₃ content exceeds 1.0%, the glass tends to have reduced clarification performance. Simultaneously, its strong oxidizing effect promotes the corrosion of platinum or platinum alloy vessels used in glassmaking and the deterioration of the forming molds. Therefore, in this invention, the Sb₂O₃ content is preferably 0-1.0%, more preferably 0-0.5%, and even more preferably 0-0.2%. In some embodiments, the Sb₂O₃ content can be 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. SnO and SnO₂ can also be used as clarifying agents, but when their content exceeds 1.0%, the tendency for glass coloring increases, or when the glass is heated, softened, and re-formed such as by molding, Sn can become the starting point for crystal nucleation, resulting in a tendency for devitrification. Therefore, the SnO2 content of the present invention is preferably 0-1.0%, more preferably 0-0.5%, and even more preferably 0-0.2%; the SnO content is preferably 0-1.0%, more preferably 0-0.5%, and even more preferably 0-0.2%. In some embodiments, the SnO content can be 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. In some embodiments, the SnO2 content can be 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.The role and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1.0%, more preferably 0-0.5%, further preferably 0-0.2%, and even more preferably free of CeO2. In some embodiments, the content of CeO2 can be 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0094] <Components that should not be present>

[0095] In the glass and chemically strengthened glass of this invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are present in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this invention to improve visible light transmittance. Therefore, it is preferable that the glass materials and chemically strengthened glass, especially those requiring transmittance in the visible light region, do not contain these oxides.

[0096] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to avoid their presence altogether, except where unavoidable contamination occurs. Consequently, the glass materials and chemically strengthened glass become virtually free of pollutants. Therefore, the glass materials and chemically strengthened glass of this invention can be manufactured, processed, and disposed of even without specific environmental countermeasures.

[0097] To achieve environmental friendliness, the glass materials and chemically strengthened glass of the present invention preferably do not contain As2O3 and PbO.

[0098] The terms "not containing" and "0%" as used herein mean that the compound, molecule, or element was not intentionally added as a raw material to the glass and chemically strengthened glass of this invention. However, as raw materials and / or equipment used in the production of glass and chemically strengthened glass, there may be certain impurities or components that are not intentionally added, and these may be present in small or trace amounts in the final glass or chemically strengthened glass. Such cases are also within the scope of protection of this patent.

[0099] The properties of the glass material and chemically strengthened glass of the present invention will be described below.

[0100] <Refractive Index and Abbe Number>

[0101] Refractive index (n) of glass materials / chemically strengthened glass d ) and Abbe number (ν d Test according to the method specified in the national standard GB / T7962.1-2010.

[0102] <Density>

[0103] The density (ρ) of glass materials / chemically strengthened glass is tested according to the method specified in the national standard GB / T7962.20-2010.

[0104] Coefficient of thermal expansion

[0105] The coefficient of thermal expansion (α) of glass materials / chemically strengthened glass -30 / 70℃ Data for -30 to 70℃ were tested according to the method specified in the national standard GB / T7962.16-2010.

[0106] <Stability under water resistance>

[0107] Water resistance stability of glass materials / chemically strengthened glass (D) W (Powder method) Tested according to the method specified in the national standard GB / T17129. In this invention, the stability of water resistance can be simply referred to as water resistance.

[0108] <Stability under acid conditions>

[0109] Acid resistance stability of glass materials / chemically strengthened glass (D) A (Powder method) Tested according to the method specified in the national standard GB / T17129. In this invention, the stability against acid can be simply referred to as acid resistance.

[0110] <Weather resistance>

[0111] The weathering resistance (CR) test method for glass materials / chemically strengthened glass is as follows: The sample is placed in a test chamber with a saturated water vapor environment of 90% relative humidity, and the temperature is alternately cyclical every 1 hour at 40–50℃, for 15 cycles. The weathering resistance category is determined based on the change in turbidity before and after the sample placement. The weathering resistance classification is shown in Table 1.

[0112] Table 1. Weather Resistance Classification Table

[0113]

[0114] <Transition Temperature>

[0115] Glass material / chemically strengthened glass transition temperature (T) gTest according to the method specified in the national standard GB / T7962.16-2010.

[0116] Knoop Hardness

[0117] Knoop Hardness (H) of Glass Materials / Chemically Strengthened Glass K The test was conducted according to the test method specified in the national standard GB / T7962.18-2010. In this invention, Knoop hardness can be simply referred to as hardness.

[0118] Young's Modulus

[0119] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.

[0120]

[0121] G = V S 2 ρ

[0122] In the formula: E is Young's modulus, Pa;

[0123] G is the shear modulus, Pa;

[0124] V T The transverse wave velocity is in m / s;

[0125] V S The longitudinal wave velocity is given in m / s.

[0126] ρ is the density of glass, in g / cm³ 3 .

[0127] <Colorization>

[0128] Short-wavelength transmission spectral characteristics of glass materials / chemically strengthened glass using chromaticity (λ) 80 And λ5) represent. λ 80 This refers to the wavelength corresponding to a glass transmittance of 80%. λ 80 The measurement was performed using a glass with a thickness of 10 ± 0.1 mm and two optically polished, parallel planes. The spectral transmittance was measured in the wavelength range from 280 nm to 700 nm, and wavelengths exhibiting 80% transmittance were recorded. Spectroscopic transmittance, or transmittance, is the value of the light incident perpendicularly to the aforementioned surface of the glass with an intensity I... in Light passes through the glass and exits from a plane with an intensity of I. out In the case of light, through I out / I in The value represents the transmittance, which also includes the surface reflection loss on the aforementioned surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in glass, λ... 80A low value means that the glass itself has very little coloration and high light transmittance.

[0129] <Effervescence>

[0130] The bubble degree of glass materials / chemically strengthened glass shall be tested according to the method specified in the national standard GB / T7962.8—2010.

[0131] <Reinforcement Layer Depth>

[0132] The depth of the strengthening layer in chemically strengthened glass was determined using energy dispersive spectroscopy (EDS). The cross-section of the chemically strengthened glass was polished, and a gold layer was sputtered using a small ion sputtering apparatus. The EDS of the glass cross-section was then measured using scanning electron microscopy (SEM) with the test lines perpendicular to the glass surface. The tested elements were Na and / or K.

[0133] During the test, the line scan results are first extracted, and the x-axis at the position of the highest energy intensity of Na or K is defined as 0. Then, the line scan results are fitted according to the following formula:

[0134]

[0135] In the formula, erf is the error function, D is the diffusion coefficient, and t is the diffusion time. Compared with the actual test results, the fitted line has the advantage of no fluctuations from random test errors. During the fitting process, the parameters n1 and n0 can be obtained. The x value corresponding to n(x) = n0 + 0.02 × (n1 - n0) on the fitted line is defined as the glass strengthening layer depth.

[0136] <Surface Quality>

[0137] The surface quality of chemically strengthened glass is a crucial characteristic for its applications. Poor surface quality not only affects performance but also reduces the yield of subsequent processes based on the strengthened glass. Samples with polished surfaces were used for surface strengthening, and the surface quality of the polished surfaces after strengthening was observed visually and categorized into four types according to Table 2.

[0138] Table 2.

[0139]

[0140]

[0141] <Flexural Strength>

[0142] The bending strength of chemically strengthened glass is tested using the following method: the three-point bending test. The sample size is 40mm × 30mm × 1mm, and both surfaces are mechanically polished. In this invention, the indenter diameter for the three-point bending test is 5mm; the span is 50mm; and the pressure displacement speed is 5mm / min.

[0143] <Drop height test>

[0144] A Φ20×2.5mm chemically strengthened glass sample is placed on a glass bearing fixture, and a 32g steel ball is dropped from a specified height. The maximum drop ball test height that the sample can withstand without breaking is the drop ball test height described in this invention. Specifically, the test is conducted starting from a drop ball test height of 0.5m, and then, without breaking, the height is successively changed to 0.5m, 0.6m, 0.7m, and above.

[0145] The glass material of this invention has the following properties:

[0146] 1) In some embodiments, the refractive index (n) of the glass material of the present invention is... d The lower limit of the refractive index (n) is 1.660, preferably 1.670, and more preferably 1.680. In some embodiments, the refractive index (n) of the glass material of the present invention is... d The upper limit for the refractive index (n) is 1.740, preferably 1.730, and more preferably 1.710. In some embodiments, the refractive index (n) is... d The possible values ​​are 1.660, 1.661, 1.663, 1.665, 1.667, 1.669, 1.670, 1.671, 1.673, 1.675, 1.677, 1.679, 1.680, 1.681, 1.683, 1.685, 1.687, 1.689, 1.690, 1.691, 1.693, 1.695, 1.697, 1.699, 1.700, and 1.70. 1, 1.703, 1.705, 1.707, 1.709, 1.710, 1.711, 1.713, 1.715, 1.717, 1.719, 1.720, 1.721, 1.723, 1.725, 1.727, 1.729, 1.730, 1.731, 1.733, 1.735, 1.737, 1.739, 1.740, etc., as well as all ranges and subranges between the above values.

[0147] 2) In some embodiments, the Abbe number (ν) of the glass material of the present invention d The lower limit for the Abbe number (ν) is 31.00, preferably 32.00, and more preferably 34.00. In some embodiments, the Abbe number (ν) of the glass material of the present invention is... d The upper limit for the Abbe number is 38.00, preferably 37.00, and more preferably 36.50. In some embodiments, the Abbe number (ν) is... dThe values ​​can be 31.00, 31.10, 31.30, 31.50, 31.70, 31.90, 32.00, 32.10, 32.30, 32.50, 32.70, 32.90, 33.00, 33.10, 33.30, 33.50, 33.70, 33.90, 34.00, 34.10, 34.30, 34.50, or 34.7. 0, 34.90, 35.00, 35.10, 35.30, 35.50, 35.70, 35.90, 36.00, 36.10, 36.30, 36.50, 36.70, 36.90, 37.00, 37.10, 37.30, 37.50, 37.70, 37.90, 38.00, etc., as well as all ranges and subranges between the above values.

[0148] 3) In some embodiments, the density (ρ) of the glass material of the present invention is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 Below. In some embodiments, the density (ρ) can be 3.60 g / cm³. 3 3.59g / cm 3 3.58g / cm 3 3.57g / cm 3 3.56g / cm 3 3.55g / cm 3 3.54g / cm 3 3.53g / cm 3 3.52g / cm 3 3.51g / cm 3 3.50g / cm 3 3.49 g / cm 3 3.48 g / cm 3 3.47 g / cm 3 3.46 g / cm 3 3.45g / cm 3 3.44 g / cm 3 3.43 g / cm 3 3.42 g / cm 3 3.41 g / cm 3 3.40 g / cm 3 3.39 g / cm 3 3.38g / cm 3 3.37 g / cm 3 3.36 g / cm 3 3.35g / cm 33.34 g / cm 3 3.33 g / cm 3 3.32g / cm 3 3.31 g / cm 3 3.30g / cm 3 3.29 g / cm 3 3.28g / cm 3 3.27 g / cm 3 3.26 g / cm 3 3.25g / cm 3 And so on, as well as all ranges and subranges between the above values.

[0149] 4) In some embodiments, the coefficient of thermal expansion (α) of the glass material of the present invention is... -30 / 70℃ ) is 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion (α) -30 / 70℃ It can be 65×10 -7 / K、66×10 -7 / K、67×10 -7 / K、68×10 -7 / K、69×10 -7 / K、70×10 -7 / K、71×10 -7 / K、72×10 -7 / K、73×10 -7 / K、74×10 -7 / K、75×10 -7 / K、76×10 -7 / K、77×10 -7 / K、78×10 -7 / K、79×10 -7 / K、80×10 -7 / K、81×10 -7 / K、82×10 -7 / K、83×10 -7 / K、84×10 -7 / K、85×10 -7 / K、86×10 -7 / K、87×10 -7 / K、88×10 -7 / K、89×10 -7 / K、90×10 -7 / K, etc., and all ranges and subranges between the above values.

[0150] 5) In some embodiments, the water resistance stability (D) of the glass material of the present invention is... W There are two or more categories, with category 1 being preferred.

[0151] 6) In some embodiments, the acid resistance stability (D) of the glass material of the present invention is... A There are two or more categories, with category 1 being preferred.

[0152] 7) In some embodiments, the weather resistance (CR) of the glass material of the present invention is Class 2 or above, preferably Class 1.

[0153] 8) In some embodiments, the transition temperature (T) of the glass material of the present invention is... g The temperature is 590°C or below, preferably 580°C or below, and more preferably 570°C or below. In some embodiments, the transition temperature (T) is... g The values ​​can be 550℃, 551℃, 553℃, 555℃, 557℃, 559℃, 560℃, 561℃, 563℃, 565℃, 567℃, 569℃, 570℃, 571℃, 573℃, 575℃, 577℃, 579℃, 580℃, 581℃, 583℃, 585℃, 587℃, 589℃, 590℃, etc., as well as all ranges and subranges between the above values.

[0154] 9) In some embodiments, the Knoop hardness (H) of the glass material of the present invention is... K ) is 520×10 7 Pa or higher, preferably 540 × 10 Pa 7 Pa or higher, more preferably 550 × 10 Pa 7 Pa or higher. In some embodiments, the Knoop hardness (H) is... K ) can be 520×10 7 Pa, 525×10 7 Pa, 530×10 7 Pa, 535×10 7 Pa, 540×10 7 Pa, 545×10 7 Pa, 550×10 7 Pa, 555×10 7 Pa, 560×10 7 Pa, 565×10 7 Pa, 570×10 7 Pa, 575×10 7 Pa, etc., and all ranges and subranges between the above values.

[0155] 10) In some embodiments, the Young's modulus (E) of the glass material of the present invention is 8500 × 10⁻⁶.7 Pa or higher, preferably 9000×10 Pa 7 Pa or higher, more preferably 9200 × 10 Pa 7 Pa or higher. In some embodiments, Young's modulus (E) can be 8500 × 10⁻⁶. 7 Pa, 8600×10 7 Pa, 8700×10 7 Pa, 8800×10 7 Pa, 8900×10 7 Pa, 9000×10 7 Pa, 9100×10 7 Pa, 9200×10 7 Pa, 9300×10 7 Pa, 9400×10 7 Pa, 9500×10 7 Pa, 9600×10 7 Pa, 9700×10 7 Pa, etc., and all ranges and subranges between the above values.

[0156] 11) In some embodiments, the λ of the glass material of the present invention 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80 The wavelength is below 410 nm. In some embodiments, the λ of the glass material... 80 It can be 390nm, 391nm, 392nm, 393nm, 394nm, 395nm, 396nm, 397nm, 398nm, 399nm, 400nm, 401nm, 402nm, 403nm, 404nm, 405nm, 406nm, 407nm, 408nm, 409nm, 410nm, 411nm, 412nm, 413nm, 414nm, 415nm, 416nm, 417nm, 418nm, 419nm, 420nm, 421nm, 422nm, 423nm, 424nm, 425nm, etc., as well as all ranges and subranges between the above values.

[0157] 12) In some embodiments, the λ5 of the glass material of the present invention is 375 nm or less, preferably 365 nm or less, and more preferably 360 nm or less. In some embodiments, the λ5 of the glass material can be 340 nm, 341 nm, 342 nm, 343 nm, 344 nm, 345 nm, 346 nm, 347 nm, 348 nm, 349 nm, 350 nm, 351 nm, 352 nm, 353 nm, 354 nm, 355 nm, 356 nm, 357 nm, 358 nm, 359 nm, 360 nm, 361 nm, 362 nm, 363 nm, 364 nm, 365 nm, 366 nm, 367 nm, 368 nm, 369 nm, 370 nm, 371 nm, 372 nm, 373 nm, 374 nm, 375 nm, etc., as well as all ranges and sub-ranges between the above values.

[0158] 13) In some embodiments, the bubble degree of the glass material of the present invention is grade A or above, preferably grade A0 or above, and more preferably grade A. 00 class.

[0159] The chemically strengthened glass of this invention has the following properties:

[0160] 1) In some embodiments, the refractive index (n) of the chemically strengthened glass of the present invention is... d The lower limit of the refractive index (n) is 1.660, preferably 1.670, and more preferably 1.680. In some embodiments, the refractive index (n) of the chemically strengthened glass of the present invention is... d The upper limit for the refractive index (n) is 1.740, preferably 1.730, and more preferably 1.710. In some embodiments, the refractive index (n) is... d The possible values ​​are 1.660, 1.661, 1.663, 1.665, 1.667, 1.669, 1.670, 1.671, 1.673, 1.675, 1.677, 1.679, 1.680, 1.681, 1.683, 1.685, 1.687, 1.689, 1.690, 1.691, 1.693, 1.695, and 1.69. 7, 1.699, 1.700, 1.701, 1.703, 1.705, 1.707, 1.709, 1.710, 1.711, 1.713, 1.715, 1.717, 1.719, 1.720, 1.721, 1.723, 1.725, 1.727, 1.729, 1.730, etc., as well as all ranges and subranges between the above values.

[0161] 2) In some embodiments, the Abbe number (ν) of the chemically strengthened glass of the present invention is... dThe lower limit for the Abbe number (ν) is 31.00, preferably 32.00, and more preferably 34.00. In some embodiments, the Abbe number (ν) of the chemically strengthened glass of the present invention is... d The upper limit for the Abbe number is 38.00, preferably 37.00, and more preferably 36.50. In some embodiments, the Abbe number (ν) is... d The values ​​can be 31.00, 31.10, 31.30, 31.50, 31.70, 31.90, 32.00, 32.10, 32.30, 32.50, 32.70, 32.90, 33.00, 33.10, 33.30, 33.50, 33.70, 33.90, 34.00, 34.10, 34.30, 34.50, or 34.7. 0, 34.90, 35.00, 35.10, 35.30, 35.50, 35.70, 35.90, 36.00, 36.10, 36.30, 36.50, 36.70, 36.90, 37.00, 37.10, 37.30, 37.50, 37.70, 37.90, 38.00, etc., as well as all ranges and subranges between the above values.

[0162] 3) In some embodiments, the density (ρ) of the chemically strengthened glass of the present invention is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 Below. In some embodiments, the density (ρ) can be 3.60 g / cm³. 3 3.59g / cm 3 3.58g / cm 3 3.57g / cm 3 3.56g / cm 3 3.55g / cm 3 3.54g / cm 3 3.53g / cm 3 3.52g / cm 3 3.51g / cm 3 3.50g / cm 3 3.49 g / cm 3 3.48 g / cm 3 3.47 g / cm 3 3.46 g / cm 3 3.45g / cm 3 3.44 g / cm 3 3.43 g / cm 3 3.42 g / cm 3 3.41 g / cm 33.40 g / cm 3 3.39 g / cm 3 3.38g / cm 3 3.37 g / cm 3 3.36 g / cm 3 3.35g / cm 3 3.34 g / cm 3 3.33 g / cm 3 3.32g / cm 3 3.31 g / cm 3 3.30g / cm 3 3.29 g / cm 3 3.28g / cm 3 3.27 g / cm 3 3.26 g / cm 3 3.25g / cm 3 And so on, as well as all ranges and subranges between the above values.

[0163] 4) In some embodiments, the coefficient of thermal expansion (α) of the chemically strengthened glass of the present invention is... -30 / 70℃ ) is 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion (α) -30 / 70℃ It can be 65×10 -7 / K、66×10 -7 / K、67×10 -7 / K、68×10 -7 / K、69×10 -7 / K、70×10 -7 / K、71×10 -7 / K、72×10 -7 / K、73×10 -7 / K、74×10 -7 / K、75×10 -7 / K、76×10 -7 / K、77×10 -7 / K、78×10 -7 / K、79×10 -7 / K、80×10 -7 / K、81×10 -7 / K、82×10 -7 / K、83×10 -7 / K、84×10 -7 / K、85×10 -7 / K、86×10-7 / K、87×10 -7 / K、88×10 -7 / K、89×10 -7 / K、90×10 -7 / K, etc., and all ranges and subranges between the above values.

[0164] 5) In some embodiments, the water resistance stability (D) of the chemically strengthened glass of the present invention is... W There are two or more categories, with category 1 being preferred.

[0165] 6) In some embodiments, the acid resistance stability (D) of the chemically strengthened glass of the present invention is... A There are two or more categories, with category 1 being preferred.

[0166] 7) In some embodiments, the weather resistance (CR) of the chemically strengthened glass of the present invention is Class 2 or above, preferably Class 1.

[0167] 8) In some embodiments, the transition temperature (T) of the chemically strengthened glass of the present invention is... g The temperature is 590°C or below, preferably 580°C or below, and more preferably 570°C or below. In some embodiments, the transition temperature (T) is... g The values ​​can be 550℃, 551℃, 553℃, 555℃, 557℃, 559℃, 560℃, 561℃, 563℃, 565℃, 567℃, 569℃, 570℃, 571℃, 573℃, 575℃, 577℃, 579℃, 580℃, 581℃, 583℃, 585℃, 587℃, 589℃, 590℃, etc., as well as all ranges and subranges between the above values.

[0168] 9) In some embodiments, the λ of the chemically strengthened glass of the present invention 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80 The wavelength is below 410 nm. In some embodiments, the λ of the chemically strengthened glass is... 80It can be 390nm, 391nm, 392nm, 393nm, 394nm, 395nm, 396nm, 397nm, 398nm, 399nm, 400nm, 401nm, 402nm, 403nm, 404nm, 405nm, 406nm, 407nm, 408nm, 409nm, 410nm, 411nm, 412nm, 413nm, 414nm, 415nm, 416nm, 417nm, 418nm, 419nm, 420nm, 421nm, 422nm, 423nm, 424nm, 425nm, etc., as well as all ranges and subranges between the above values.

[0169] 10) In some embodiments, the λ5 of the chemically strengthened glass of the present invention is 375 nm or less, preferably 365 nm or less, and more preferably 360 nm or less. In some embodiments, the λ5 of the chemically strengthened glass can be 340 nm, 341 nm, 342 nm, 343 nm, 344 nm, 345 nm, 346 nm, 347 nm, 348 nm, 349 nm, 350 nm, 351 nm, 352 nm, 353 nm, 354 nm, 355 nm, 356 nm, 357 nm, 358 nm, 359 nm, 360 nm, 361 nm, 362 nm, 363 nm, 364 nm, 365 nm, 366 nm, 367 nm, 368 nm, 369 nm, 370 nm, 371 nm, 372 nm, 373 nm, 374 nm, 375 nm, etc., as well as all ranges and sub-ranges between the above values.

[0170] 11) In some embodiments, the bubble degree of the chemically strengthened glass of the present invention is grade A or above, preferably grade A0 or above, and more preferably grade A. 00 class.

[0171] 12) In some embodiments, the depth of the strengthening layer of the chemically strengthened glass of the present invention is 15 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 to 50 μm. In some embodiments, the strengthening layer depth of the chemically strengthened glass can be 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm, 49μm, 50μm, etc., as well as all ranges and subranges between the above values.

[0172] 13) In some embodiments, the flexural strength of the chemically strengthened glass of the present invention is 250 MPa or more, preferably 300 MPa or more, more preferably 350 MPa or more, and even more preferably 450-500 MPa. In some embodiments, the flexural strength of the chemically strengthened glass can be 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa, 300 MPa, 310 MPa, 320 MPa, 330 MPa, 340 MPa, 350 MPa, 360 MPa, 370 MPa, 380 MPa, 390 MPa, 400 MPa, 410 MPa, 420 MPa, 430 MPa, 440 MPa, 450 MPa, 460 MPa, 470 MPa, 480 MPa, 490 MPa, 500 MPa, etc., as well as all ranges and sub-ranges between the above values.

[0173] 14) In some embodiments, the drop ball test height of the chemically strengthened glass of the present invention is 1.0m or more, preferably 1.3m or more, more preferably 1.5m or more, and even more preferably 1.8m or more. In some embodiments, the drop ball test height of the chemically strengthened glass can be 1.0m, 1.1m, 1.2m, 1.3m, 1.4m, 1.5m, 1.6m, 1.7m, 1.8m, 1.9m, 2.0m, 2.1m, 2.2m, 2.3m, etc., as well as all ranges and sub-ranges between the above values.

[0174] 15) In some embodiments, the surface quality of the chemically strengthened glass of the present invention is Class 2 or above, preferably Class 1 or above.

[0175] [Manufacturing methods for glass materials and chemically strengthened glass]

[0176] The manufacturing method of the glass material of this invention is as follows: The glass of this invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials. After being prepared according to conventional methods, the prepared furnace charge is put into a melting furnace (such as a platinum or platinum alloy crucible) at 1200-1400℃ for melting. After clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.

[0177] The glass material of the present invention can also be formed by well-known methods. In some embodiments, the glass material described herein can be manufactured into glass preforms by various processes, including but not limited to sheets, lenses, prisms, etc. These processes include, but are not limited to, slot drawing, float glass, roll forming, and other processes known in the art for forming sheets, lenses, and prisms. Alternatively, the glass material can be formed by float glass or roll forming methods known in the art. The glass material and glass preforms of the present invention can have any reasonably useful thickness, shape, or structure, such as 2D, 2.5D, or 3D.

[0178] The glass material of the present invention can be used to manufacture sheet glass preforms by methods such as grinding or polishing, but the method of manufacturing glass preforms is not limited to these methods.

[0179] Glass preforms can be manufactured from the produced glass material using methods such as grinding, hot pressing, or precision stamping. Specifically, glass preforms can be manufactured by machining the glass material, such as grinding and polishing; or by making a preform from the glass material for molding, then hot pressing and grinding the preform; or by precision stamping a preform made through grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.

[0180] The chemically strengthened glass of this invention is obtained by chemically strengthening the glass material or glass preform of this invention. The chemical strengthening process of this invention includes immersing the glass material or glass preform in molten potassium salt and / or sodium salt at a certain temperature (i.e., the chemical strengthening temperature) for a certain period of time.

[0181] The chemical strengthening treatment of glass materials or glass preforms of the present invention includes a two-step chemical strengthening process using molten salts containing KNO3 and / or NaNO3.

[0182] The first step of chemical strengthening involves Li-Na exchange, in which the glass material or glass preform is immersed in a molten salt containing NaNO3. This molten salt can be pure NaNO3 or a mixed molten salt composed of NaNO3, KNO3, or other known common salt bath components and salt bath additives. This first step of chemical strengthening allows for high-stress-depth ion exchange in the glass material, increasing its resistance to fracture, puncture, and crack propagation. For chemical strengthening, higher temperatures result in faster ion diffusion and a deeper stress layer. However, excessively high temperatures can lead to stress relaxation and surface damage from salt bath corrosion, affecting the subsequent performance as a glass component. Conversely, low temperatures result in slow ion diffusion, a shallow stress layer, and insignificant strengthening effects. Therefore, the preferred first-step chemical strengthening temperature in this invention is 400–500°C, more preferably 420–480°C, and even more preferably 430–470°C. Appropriately increasing the chemical strengthening time can improve the stress layer depth and the strengthening effect. However, excessively long chemical strengthening times can easily lead to the volatilization and decomposition of the salt bath, causing impurities to adhere to the glass material surface and significantly reducing the salt bath life. Therefore, the preferred first-step chemical strengthening time of this invention is 1 to 11 hours, more preferably 1 to 9 hours, and even more preferably 1 to 7 hours.

[0183] The second step of chemical strengthening involves Na-K exchange. The glass material or preform, after the first step of chemical strengthening, is immersed in a molten salt containing KNO3. This molten salt can be pure KNO3 or a mixed molten salt composed of KNO3, NaNO3, or other known common salt bath components and additives. Between the first and second steps of chemical strengthening, the glass material or preform can be cleaned and annealed. This second step, using this chemical strengthening method, enables ion exchange with high surface stress in the glass material, increasing its drop resistance and impact resistance. For Na-K chemical strengthening, lower temperatures result in slower ion diffusion in the glass, a lower stress layer, higher surface ion concentration, and easier achievement of high surface compressive stress. However, excessively low strengthening temperatures reduce the ion exchange coefficient of the glass, making it impossible to achieve a usable chemically strengthened stress layer. Excessively high strengthening temperatures lead to stress relaxation, reduced surface compressive stress, and easy volatilization and decomposition of the salt bath, causing impurities to adhere to the glass surface and significantly reducing the salt bath life. Therefore, the chemical strengthening temperature in this invention is preferably 420–520°C, more preferably 440–500°C, and even more preferably 450–490°C. The shorter the chemical strengthening time, the shallower the stress layer depth and the greater the surface compressive stress. However, too short a chemical strengthening time will result in an insignificant strengthening effect and an inability to obtain an effective stress layer. Too long a chemical strengthening time can easily lead to stress relaxation, as well as surface damage and surface deposits due to severe salt bath volatilization and decomposition. Therefore, the glass of this invention should ideally have a low strengthening time to obtain a large surface compressive stress and prevent salt bath deterioration. The chemical strengthening time of the glass of this invention is preferably 10 minutes to 2.5 hours, more preferably 20 minutes to 2 hours.

[0184] [Glass prefabrication and glass components]

[0185] Glass preforms can be manufactured from the produced glass material using methods such as direct drip forming, grinding, or hot pressing. Specifically, glass preforms can be manufactured by directly and precisely dripping molten glass material, by machining such as grinding and polishing, or by hot pressing a preform made from the glass material for compression molding, followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.

[0186] As described above, the glass material and chemically strengthened glass of the present invention are useful for various glass components and optical designs. In particular, it is preferred to form a preform from the glass material of the present invention, and to use the preform for hot pressing, precision stamping, etc., to manufacture glass components such as lenses and prisms, or to manufacture glass components from the chemically strengthened glass of the present invention.

[0187] Both the glass preform and the glass element of the present invention are formed from the glass material or chemically strengthened glass described above. The glass preform of the present invention possesses the excellent properties of the glass material; the glass element of the present invention possesses the excellent properties of the glass material or chemical strengthening properties, and can provide various lenses, prisms, diffraction gratings and other glass elements with high optical value.

[0188] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.

[0189] [Optical Equipment]

[0190] The glass materials, chemically strengthened glass, glass preforms, and glass components of this invention can be used to manufacture optical devices such as photographic equipment, portable electronic devices (e.g., mobile phones, watches), video cameras, display devices, and monitoring equipment. The glass materials, chemically strengthened glass, glass preforms, and glass components of this invention are suitable for use in automotive lighting instruments and optical devices, and can be applied in automotive and other fields. The glass materials, chemically strengthened glass, glass preforms, and glass components of this invention are also suitable for use in optical devices such as micro-projection, micro-imaging (camera / photography), micro-lighting, optical waveguides, and AR imaging systems.

[0191] [Example]

[0192] <Examples of Glass Materials>

[0193] To further illustrate and explain the technical solution of the present invention, the following non-limiting embodiments are provided.

[0194] In this embodiment, glass materials with the compositions shown in Tables 3 to 5 were obtained using the glass material manufacturing method described above. Furthermore, the properties of each glass were measured using the testing method described in this invention, and the measurement results are shown in Tables 3 to 5.

[0195] Table 3.

[0196]

[0197]

[0198]

[0199] Table 4.

[0200]

[0201]

[0202] Table 5.

[0203]

[0204]

[0205] <Examples of Chemically Strengthened Glass>

[0206] To further illustrate and explain the technical solution of the present invention, the following non-limiting embodiments are provided.

[0207] In this embodiment, chemically strengthened glass with the compositions shown in Tables 6 to 8 was obtained using the aforementioned method for manufacturing chemically strengthened glass. Furthermore, the properties of each chemically strengthened glass were measured using the testing method described in this invention, and the measurement results are shown in Tables 6 to 8.

[0208] Table 6.

[0209]

[0210]

[0211]

[0212] Table 7.

[0213]

[0214]

[0215] Table 8.

[0216]

[0217]

[0218] <Example of Glass Prefabricated Components>

[0219] The glass obtained in the glass material examples in Tables 3 and 4 is used, for example, by grinding or by molding such as hot pressing or precision stamping, to produce preforms of various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0220] <Example of Glass Component>

[0221] Annealing these preforms obtained from the above glass preform examples reduces internal stress in the glass while fine-tuning the refractive index, so that optical properties such as the refractive index reach the desired values.

[0222] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. An anti-reflective film can also be coated on the surface of the resulting glass elements.

[0223] <Optical Equipment Examples>

[0224] The glass elements obtained from the above-described glass element embodiments can be optically designed to form optical components or assemblies by using one or more glass elements. These components can be used in, for example, imaging devices, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices that include such circuits and chips.

Claims

1. A glass material, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 28.0–42.0%; B2O3: 1.0–9.5%; ZrO2: 1.0–10.0%; La2O3: greater than or equal to 1.0% but less than 10.0%; Nb2O5: 2.0–14.5%. ZnO: 2.0–14.5%; TiO2: 3.0–16.0%; RO: 2.0–22.0%; Rn2O: 2.0–24.0%, wherein ZnO / La2O3 is 0.30–8.00, RO is the total content of MgO, CaO, SrO, and BaO, and Rn2O is the total content of Li2O, Na2O, and K2O.

2. The glass material according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: Al2O3: 0–8.0%; and / or Y2O3: 0–8.0%; and / or Gd2O3: 0–5.0%; and / or P2O5: 0–5.0%; and / or WO3: 0–3.0%; and / or clarifying agent: 0–1.0%, wherein the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

3. The glass material according to claim 1 or 2, characterized in that, Its components are expressed as a weight percentage and satisfy one or more of the following 13 conditions: 1) The ZnO / La2O3 ratio is 0.50 to 5.00, preferably 0.80 to 3.50, and more preferably 1.00 to 2.50; 2) The SiO2 / (B2O3+BaO) ratio is 1.50 to 8.00, preferably 1.80 to 6.00, more preferably 2.00 to 5.50, and even more preferably 2.80 to 3.80; 3) The ratio of (ZnO+BaO) / SiO2 is 0.10 to 0.80, preferably 0.20 to 0.70, and more preferably 0.30 to 0.60; 4) The ratio of (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.30~3.00, preferably 0.35~2.00, more preferably 0.40~1.40, and even more preferably 0.50~1.00; 5) The ratio of (La2O3+Na2O) / Nb2O5 is 0.50 to 7.00, preferably 0.80 to 5.00, more preferably 1.00 to 3.50, and even more preferably 1.10 to 2.00; 6) The ratio of (La2O3+BaO) / Na2O is 0.30 to 7.00, preferably 0.50 to 5.00, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50; 7) The ratio of (Nb2O5+TiO2+CaO) / SiO2 is 0.15 to 1.00, preferably 0.20 to 0.80, and more preferably 0.30 to 0.

70. 8) The La2O3 / TiO2 ratio is 0.20 to 2.50, preferably 0.20 to 2.00, more preferably 0.30 to 1.50, and even more preferably 0.30 to 1.00; 9) The Y2O3 / Na2O ratio is 0.05 to 2.00, preferably 0.08 to 1.50, more preferably 0.10 to 1.00, and even more preferably 0.10 to 0.70; 10) The Y2O3 / SrO ratio is 0.10 to 5.00, preferably 0.20 to 4.00, more preferably 0.30 to 2.00, and even more preferably 0.40 to 1.00; 11)(Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 1.00~9.00, preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.00~7.50, more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.50~6.00, and even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 3.20~4.80; 12) The ratio of 5×P2O5 / Al2O3 is 0.10 to 6.00, preferably 0.20 to 3.50, more preferably 0.30 to 2.50, and even more preferably 0.50 to 1.50; 13) The ratio of (Li2O+K2O) / Al2O3 is 0.20 to 5.00, preferably 0.50 to 3.50, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.

50.

4. The glass material according to claim 1 or 2, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 30.5–39.5%, preferably SiO2: 32.0–37.0%; and / or B2O3: 2.0–8.0%, preferably B2O3: 2.5–7.0%; and / or ZrO2: 2.0–8.5%, preferably ZrO2: 3.0–7.0%; and / or La2O3: 2.0–9.0%, preferably La2O3: 3.0–8.0%; and / or Nb Nb2O5: 4.0–12.0%, preferably Nb2O5: 5.0–10.0%; and / or ZnO: 4.0–12.0%, preferably ZnO: 5.0–10.0%; and / or TiO2: 5.0–15.0%, preferably TiO2: 7.0–13.0%; and / or RO: 3.0–18.0%, preferably RO: 5.0–15.0%; and / or Rn2O: 5.0–20.0%, preferably Rn2O : 7.0–15.0%; and / or Al2O3: 0.1–6.0%, preferably Al2O3: 0.5–4.0%; and / or Y2O3: greater than 0% but less than or equal to 6.0%, preferably Y2O3: 0.1–4.0%; and / or Gd2O3: 0–3.0%, preferably Gd2O3: 0–1.0%, more preferably not containing Gd2O3; and / or P2O5: 0–3.0%, preferably P2O5: greater than 0% but Less than or equal to 2.0%; and / or WO3: 0 to 2.0%, preferably WO3: 0 to 1.0%, more preferably WO3-free; and / or clarifying agent: 0 to 0.5%, preferably 0 to 0.2%, wherein RO is the total content of MgO, CaO, SrO, and BaO, Rn2O is the total content of Li2O, Na2O, and K2O, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

5. The glass material according to claim 1 or 2, characterized in that, Its components are expressed as weight percentages, wherein: BaO: 1.0–12.0%, preferably BaO: 2.0–10.0%, more preferably BaO: 3.0–8.0%; and / or SrO: 0–10.0%, preferably SrO: 0.5–8.0%, more preferably SrO: 1.0–6.0%; and / or CaO: 0–5.0%, preferably CaO: 0–3.0%, more preferably CaO: 0–2.0%, further preferably free of CaO; and / or MgO: 0–5.0%, preferably MgO: 0–4.0%, more preferably... MgO: 0-2.0%, more preferably MgO-free; and / or Li2O: greater than 0% but less than or equal to 8.0%, preferably Li2O: greater than 0% but less than or equal to 6.0%, more preferably Li2O: 0.1-4.0%; and / or Na2O: 2.0-15.0%, preferably Na2O: 4.0-12.0%, more preferably Na2O: 5.0-10.0%; and / or K2O: greater than 0% but less than or equal to 8.0%, preferably K2O: 0.1-6.0%, more preferably K2O: 0.5-4.5%.

6. The glass material according to claim 1 or 2, characterized in that, The refractive index n of the glass material d The value is 1.660–1.740, preferably 1.670–1.730, more preferably 1.680–1.710; and / or the Abbe number v d The content is 31.00–38.00, preferably 32.00–37.00, more preferably 34.00–36.50; and / or the density ρ is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 The following are required: and / or weather resistance (CR) is Class 2 or above, preferably Class 1; and / or water resistance stability (D). W It is classified as Class 2 or above, preferably Class 1; and / or acid resistance stability D A It is of two or more classes, preferably of one class; and / or the coefficient of thermal expansion α -30 / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K below; and / or transition temperature T g Temperature is below 590°C, preferably below 580°C, and more preferably below 570°C; and / or Knoop hardness H K 520×10 7 Pa or higher, preferably 540 × 10 Pa 7 Pa or higher, more preferably 550 × 10 Pa 7 Pa or above; and / or Young's modulus E is 8500 × 10⁻⁶. 7 Pa or higher, preferably 9000×10 Pa 7 Pa or higher, more preferably 9200 × 10 Pa. 7 Pa or above; and / or λ 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80 The wavelength is 410 nm or less; and / or λ5 is 375 nm or less, preferably 365 nm or less, more preferably 360 nm or less; and / or the bubble density is A grade or higher, preferably A0 grade or higher, more preferably A. 00 class.

7. A glass precast component, characterized in that, It is made of the glass material described in any one of claims 1 to 6.

8. Chemically strengthened glass, characterized in that, It is made of the glass material described in any one of claims 1 to 6, or of the glass preform described in claim 7.

9. The chemically strengthened glass according to claim 8, characterized in that, The chemically strengthened glass has a strengthening layer depth of 15 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 to 50 μm; and / or a bending strength of 250 MPa or more, preferably 300 MPa or more, more preferably 350 MPa or more, and even more preferably 450 to 500 MPa; and / or a drop ball test height of 1.0 m or more, preferably 1.3 m or more, more preferably 1.5 m or more, and even more preferably 1.8 m or more; and / or a surface quality of Class 2 or more, preferably Class 1 or more.

10. Chemically strengthened glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 28.0–42.0%; B2O3: 1.0–9.5%; ZrO2: 1.0–10.0%; La2O3: greater than or equal to 1.0% but less than 10.0%; Nb2O5: 2.0–14.5%. ZnO: 2.0–14.5%; TiO2: 3.0–16.0%; RO: 2.0–22.0%; Rn2O: 2.0–24.0%, wherein ZnO / La2O3 is 0.30–8.00, RO is the total content of MgO, CaO, SrO, and BaO, and Rn2O is the total content of Li2O, Na2O, and K2O.

11. The chemically strengthened glass according to claim 10, characterized in that, Its components, expressed as a weight percentage, also contain: Al2O3: 0–8.0%; and / or Y2O3: 0–8.0%; and / or Gd2O3: 0–5.0%; and / or P2O5: 0–5.0%; and / or WO3: 0–3.0%; and / or clarifying agent: 0–1.0%, wherein the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

12. The chemically strengthened glass according to claim 10 or 11, characterized in that, Its components are expressed as a weight percentage and satisfy one or more of the following 13 conditions: 1) The ZnO / La2O3 ratio is 0.50 to 5.00, preferably 0.80 to 3.50, and more preferably 1.00 to 2.50; 2) The SiO2 / (B2O3+BaO) ratio is 1.50 to 8.00, preferably 1.80 to 6.00, more preferably 2.00 to 5.50, and even more preferably 2.80 to 3.80; 3) The ratio of (ZnO+BaO) / SiO2 is 0.10 to 0.80, preferably 0.20 to 0.70, and more preferably 0.30 to 0.60; 4) The ratio of (Nb2O5+ZrO2) / (ZnO+TiO2) is 0.30~3.00, preferably 0.35~2.00, more preferably 0.40~1.40, and even more preferably 0.50~1.00; 5) The ratio of (La2O3+Na2O) / Nb2O5 is 0.50 to 7.00, preferably 0.80 to 5.00, more preferably 1.00 to 3.50, and even more preferably 1.10 to 2.00; 6) The ratio of (La2O3+BaO) / Na2O is 0.30 to 7.00, preferably 0.50 to 5.00, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.50; 7) The ratio of (Nb2O5+TiO2+CaO) / SiO2 is 0.15 to 1.00, preferably 0.20 to 0.80, and more preferably 0.30 to 0.

70. 8) The La2O3 / TiO2 ratio is 0.20 to 2.50, preferably 0.20 to 2.00, more preferably 0.30 to 1.50, and even more preferably 0.30 to 1.00; 9) The Y2O3 / Na2O ratio is 0.05 to 2.00, preferably 0.08 to 1.50, more preferably 0.10 to 1.00, and even more preferably 0.10 to 0.70; 10) The Y2O3 / SrO ratio is 0.10 to 5.00, preferably 0.20 to 4.00, more preferably 0.30 to 2.00, and even more preferably 0.40 to 1.00; 11)(Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 1.00~9.00, preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.00~7.50, more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 2.50~6.00, and even more preferably (Nb2O5+Na2O+La2O3+Y2O3) / (BaO+CaO) is 3.20~4.80; 12) The ratio of 5×P2O5 / Al2O3 is 0.10 to 6.00, preferably 0.20 to 3.50, more preferably 0.30 to 2.50, and even more preferably 0.50 to 1.50; 13) The ratio of (Li2O+K2O) / Al2O3 is 0.20 to 5.00, preferably 0.50 to 3.50, more preferably 0.80 to 3.00, and even more preferably 1.00 to 2.

50.

13. The chemically strengthened glass according to claim 10 or 11, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 30.5–39.5%, preferably SiO2: 32.0–37.0%; and / or B2O3: 2.0–8.0%, preferably B2O3: 2.5–7.0%; and / or ZrO2: 2.0–8.5%, preferably ZrO2: 3.0–7.0%; and / or La2O3: 2.0–9.0%, preferably La2O3: 3.0–8.0%; and / or Nb Nb2O5: 4.0–12.0%, preferably Nb2O5: 5.0–10.0%; and / or ZnO: 4.0–12.0%, preferably ZnO: 5.0–10.0%; and / or TiO2: 5.0–15.0%, preferably TiO2: 7.0–13.0%; and / or RO: 3.0–18.0%, preferably RO: 5.0–15.0%; and / or Rn2O: 5.0–20.0%, preferably Rn2O : 7.0–15.0%; and / or Al2O3: 0.1–6.0%, preferably Al2O3: 0.5–4.0%; and / or Y2O3: greater than 0% but less than or equal to 6.0%, preferably Y2O3: 0.1–4.0%; and / or Gd2O3: 0–3.0%, preferably Gd2O3: 0–1.0%, more preferably not containing Gd2O3; and / or P2O5: 0–3.0%, preferably P2O5: greater than 0% but Less than or equal to 2.0%; and / or WO3: 0 to 2.0%, preferably WO3: 0 to 1.0%, more preferably WO3-free; and / or clarifying agent: 0 to 0.5%, preferably 0 to 0.2%, wherein RO is the total content of MgO, CaO, SrO, and BaO, Rn2O is the total content of Li2O, Na2O, and K2O, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.

14. The chemically strengthened glass according to claim 10 or 11, characterized in that, Its components are expressed as weight percentages, wherein: BaO: 1.0–12.0%, preferably BaO: 2.0–10.0%, more preferably BaO: 3.0–8.0%; and / or SrO: 0–10.0%, preferably SrO: 0.5–8.0%, more preferably SrO: 1.0–6.0%; and / or CaO: 0–5.0%, preferably CaO: 0–3.0%, more preferably CaO: 0–2.0%, further preferably free of CaO; and / or MgO: 0–5.0%, preferably MgO: 0–4.0%, more preferably... MgO: 0-2.0%, more preferably MgO-free; and / or Li2O: greater than 0% but less than or equal to 8.0%, preferably Li2O: greater than 0% but less than or equal to 6.0%, more preferably Li2O: 0.1-4.0%; and / or Na2O: 2.0-15.0%, preferably Na2O: 4.0-12.0%, more preferably Na2O: 5.0-10.0%; and / or K2O: greater than 0% but less than or equal to 8.0%, preferably K2O: 0.1-6.0%, more preferably K2O: 0.5-4.5%.

15. The chemically strengthened glass according to claim 10 or 11, characterized in that, The refractive index n of the chemically strengthened glass d The value is 1.660–1.740, preferably 1.670–1.730, more preferably 1.680–1.710; and / or the Abbe number v d The content is 31.00–38.00, preferably 32.00–37.00, more preferably 34.00–36.50; and / or the density ρ is 3.60 g / cm³. 3 The preferred value is 3.50 g / cm³. 3 The preferred value is 3.40 g / cm³. 3 The following are required: and / or weather resistance (CR) is Class 2 or above, preferably Class 1; and / or water resistance stability (D). W It is classified as Class 2 or above, preferably Class 1; and / or acid resistance stability D A It is of two or more classes, preferably of one class; and / or the coefficient of thermal expansion α -30 / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K below; and / or transition temperature T g The temperature is below 590°C, preferably below 580°C, and more preferably below 570°C; and / or λ 80 For wavelengths below 425nm, λ is preferred. 80 For wavelengths below 415nm, λ is preferred. 80 The wavelength is 410 nm or less; and / or λ5 is 375 nm or less, preferably 365 nm or less, more preferably 360 nm or less; and / or the bubble density is A grade or higher, preferably A0 grade or higher, more preferably A. 00 Grade; and / or the depth of the reinforcing layer is 15 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 to 50 μm; and / or the flexural strength is 250 MPa or more, preferably 300 MPa or more, more preferably 350 MPa or more, and even more preferably 450 to 500 MPa; and / or the drop ball test height is 1.0 m or more, preferably 1.3 m or more, more preferably 1.5 m or more, and even more preferably 1.8 m or more; and / or the surface quality is Class 2 or more, preferably Class 1 or more.

16. A glass element, characterized in that, It is made of the glass material described in any one of claims 1 to 6, or of the glass preform described in claim 7, or of the chemically strengthened glass described in any one of claims 8 to 15.

17. An optical device, characterized in that, It contains the glass material according to any one of claims 1 to 6, or the chemically strengthened glass according to any one of claims 8 to 15, or the glass element according to claim 16.

18. The method for manufacturing chemically strengthened glass according to any one of claims 8 to 15, characterized in that, The method includes the following steps: forming a glass material, chemically strengthening the glass material, or chemically strengthening the glass material after processing it into a glass preform.

19. The method for manufacturing chemically strengthened glass according to claim 18, characterized in that, The chemical strengthening treatment includes a two-step chemical strengthening process in which the glass material or glass preform is immersed in a molten salt containing KNO3 and / or NaNO3. The first step of chemical strengthening involves immersing the glass material or glass preform in the molten salt containing NaNO3 at a temperature of 400–500°C, preferably 420–480°C, more preferably 430–470°C, and for a duration of 1–11 hours, preferably 1–9 hours, more preferably 1–7 hours. The second step of chemical strengthening involves immersing the glass material or glass preform after the first step of chemical strengthening in the molten salt containing KNO3 at a temperature of 420–520°C, preferably 440–500°C, more preferably 450–490°C, and for a duration of 10 minutes to 2.5 hours, preferably 20 minutes to 2 hours.